2016
DOI: 10.1007/s12032-016-0782-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL-37 in cancer

Abstract: Interleukin 37 (IL-37) is a new member of the IL-1 family which all have a similar β-barrel structure. Since its discovery, IL-37 has been studied extensively in immunological field. It has been established that IL-37 possesses anti-inflammatory characteristics both in innate immune response as well as in acquired immune responses by downregulating pro-inflammatory molecules. This review will discuss the role of IL-37 in immunological processes and neoplastic pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…It has been well established that inflammation is closely related to carcinogenesis . As an anti‐inflammatory cytokine, many studies have suggested the antitumor role of IL‐37 in various tumor types, which have been reviewed previously . Here, we will describe the most recent progress for the role of IL‐37 in fibrosarcoma, breast cancer, lung cancer, ovarian cancer, renal cell carcinoma (RCC), oral squamous cell carcinoma (OSCC), cervical cancer, colon cancer, multiple myeloma (MM), prostate cancer, and HCC.…”
Section: Il‐37 In Tumormentioning
confidence: 96%
See 1 more Smart Citation
“…It has been well established that inflammation is closely related to carcinogenesis . As an anti‐inflammatory cytokine, many studies have suggested the antitumor role of IL‐37 in various tumor types, which have been reviewed previously . Here, we will describe the most recent progress for the role of IL‐37 in fibrosarcoma, breast cancer, lung cancer, ovarian cancer, renal cell carcinoma (RCC), oral squamous cell carcinoma (OSCC), cervical cancer, colon cancer, multiple myeloma (MM), prostate cancer, and HCC.…”
Section: Il‐37 In Tumormentioning
confidence: 96%
“…44,45 As an anti-inflammatory cytokine, many studies have suggested the antitumor role of IL-37 in various tumor types, which have been reviewed previously. 46,47 Here, we will describe the most recent progress for the role of IL-37 in fibrosarcoma, breast cancer, lung cancer, ovarian cancer, renal cell carcinoma (RCC), oral squamous cell carcinoma (OSCC), cervical cancer, colon cancer, multiple myeloma (MM), prostate cancer, and HCC. We will also discuss in details about the recent studies on the immune regulatory function of IL-37 in antitumor immune response, as well as its role in angiogenesis.…”
Section: Il-37 In Tumormentioning
confidence: 99%
“…Conversely, anti‐inflammatory IL‐37 might suppress tumorigenesis by inhibiting protumorigenic inflammation. Indeed, the protective role of IL‐37 in cancer has been reported when IL‐37 was transfected into cancer cells, or when recombinant IL‐37 was administered in animal models of cancers (summarized in review papers by Ding et al and Abulkhir et al). However, only limited studies have used cancer patient samples to investigate IL‐37 .…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 overexpression restored the CC cell growth and invasion, and increased the transcription of TNF-α and IL-1β (12). IL-37 expression is upregulated in breast carcinoma tissues, which indicates that this cytokine may have a role in tumor progression (9,81). However, IL-37 expression is downregulated in lung cancer tissues and, it suppresses tumorigenesis in non-small cell lung cancer (NSCLC) in vivo.…”
Section: Chronic Inflammatory and Autoimmune Disordersmentioning
confidence: 99%